2016
DOI: 10.6000/1927-5129.2016.12.25
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Suitable Substrate for Seedling Tuber Production by True Potato Seed through Nursery Raising

Abstract: To determine the suitable substrate, five growth substrates viz. Soil + Sand, Soil + FYM, Soil + Sand + FYM, Soil + PM (Poultry manure) and Soil + Sand + PM were used to grow the three true potato seed (TPS) genotypes viz. TPS-9802, TPS-9804 and TPS-9805. Results of the interactive effect of genotypes x substrates on plant and tuber traits concluded that maximum germination (90.5 %), plant height (46.3 cm), micro tubers (212.7), small tubers (45.7), medium tubers (28.2), large tubers (10.2) and total tubers (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Highest and lowest values of these parameters at all the growth stages might be due to their varietal character, the capacity of root regeneration, their adoptability to different soil and environmental conditions and response to the available nutrients which might influenced the leaf length and width [28]. These results are in close conformity with the findings of Kundu [29], Jamro et al [30] and Beck [31] in potato.…”
Section: Growth Parameterssupporting
confidence: 89%
See 2 more Smart Citations
“…Highest and lowest values of these parameters at all the growth stages might be due to their varietal character, the capacity of root regeneration, their adoptability to different soil and environmental conditions and response to the available nutrients which might influenced the leaf length and width [28]. These results are in close conformity with the findings of Kundu [29], Jamro et al [30] and Beck [31] in potato.…”
Section: Growth Parameterssupporting
confidence: 89%
“…Gebremedhin et al [40] who concluded that the number of tubers among the cultivars could be genetic. The same trend was found by Nizamuddin et al [17], Moeini et al [41], Bilate and Mulualem [42] and Jamro et al [30] in potato. The results from ( Tekalign [43] reported that yield differences among varieties were attributed to the inherent yield potential of varieties and growing environment as well as the interaction of varieties x environment in potato.…”
Section: Yield Parameterssupporting
confidence: 85%
See 1 more Smart Citation
“…potato "Burren" to study the effect of the number of times for spraying the humic acid at a concentration of 1 g L -1 ( 0, 2, 4 times) they found spraying with four times over the rest of the treatments, increased in plant length (22.6 cm), number of leaves (25.1 leaves of plant-1 ) and in number of tubers (14.6 tuber plant -1 ) also exceeded the treatment of the location of spray (vegetables growth + soil) in the length of the plant and the number of leaves and the number of tubers, 20.1 cm , 23.8 leaf and 14.7 tuber plant -1 respectively comparison with control (14.0 cm, 19.7 leaf and 12.3 tuber plant -1 respectively). In a study by [6] to evaluate three potato genotypes produced by TPS in the nursery (9802, 9804, 9805), the highest values of germination rate and plant high was in 9804 (80% and 39 cm plant -1 respectively) The number of tubers was reduced from small to large, the number of tubers in 9804 was 179.5 mini tubers, 37.7 small tubers, 20.4 moderated tubers, 7.4 large tubers with 245 tubers m 2 , followed by 9805 (229.7 tubers m 2 ) The total yield was reached to 25.7, 28.1, 23.6 tan ha -1 for genotypes 9805, 9804 and 9802, respectively. [7] noted in his study of spraying the organic nutrient solution Siapton on five varieties of potatoes (Riviera, Fuller, Arizona, Arnova, Hormuz) with three concentrations (0, 2, 4 ml l-1) that spraying the solution at a concentration of 4 ml l -1 led to a significant increase in the dry weight, chlorophyll content and leaf area (162.7 gm plant -1 , 105.23 mg 100 gm -1 and 45.86 dm 2 plant -1 , respectively, and in the yield traits, the average tuber weight, plant yield were 157.3 g tuber -1 and 1490 g plant -1 .…”
Section: Introductionmentioning
confidence: 98%